Harmonic and (ϕ, ϕ´)-holomorphic Maps on Some Generalization of Contact Metric Manifolds (European Journal of Pure and Applied Mathematics, 2017)
We study (ϕ, ϕ´)-holomorphic and harmonic maps on almost contact metric manifoldssatisfying dη + dηoϕ ⊗ ϕ = 2Φ. It should be noted that these manifolds are not necessarily contact metric manifolds. Examples of such manifolds are nearly Sasakain and quasi contact metric manifolds.